Phosphatidylinositol (4,5) bisphosphate regulates HIV-1 Gag targeting to the plasma membrane - Ono, Akira (National Academy of Sciences, 2004)
A critical early event in the HIV type 1 (HIV-1) particle assembly pathway is the targeting of the Gag protein to the site of virus assembly. In many cell types, assembly takes place predominantly at the plasma membrane. Cellular factors that regulate Gag targeting remain undefined. The phosphoinositide phosphatidylinositol (4,5) bisphosphate [PI(4,5)P(2)] controls the plasma membrane localization of a number of cellular proteins. To explore the possibility that this lipid may be involved in Gag targeting and virus particle production, we overexpressed phosphoinositide 5-phosphatase IV, an enzyme that depletes cellular PI(4,5)P(2), or overexpressed a constitutively active form of Arf6 (Arf6/Q67L), which induces the formation of PI(4,5)P(2)-enriched endosomal structures. Both approaches severely reduced virus production. Upon 5-phosphatase IV overexpression, Gag was no longer localized on the plasma membrane but instead was retargeted to late endosomes. Strikingly, in cells expressing Arf6/Q67L, Gag was redirected to the PI(4,5)P(2)-enriched vesicles and HIV-1 virions budded into these vesicles. These results demonstrate that PI(4,5)P(2) plays a key role in Gag targeting to the plasma membrane and thus serves as a cellular determinant of HIV-1 particle production.